2006
DOI: 10.1037/0022-0663.98.1.112
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental effects of serial naming and phonological awareness on early reading outcomes.

Abstract: The current study involved 281 early-school-age twin pairs (118 monozygotic, 163 same-sex dizygotic) participating in the ongoing Western Reserve Reading Project (S. A. Petrill, K. DeaterDeckard, L. A. Thompson, & C. Schatschneider, 2006). Twins were tested in their homes by separate examiners on a battery of reading-related skills including phonological awareness, rapid automatized naming, word knowledge, and phonological decoding. Results suggested that a core genetic factor accounted for a significant porti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 33 publications
5
58
2
Order By: Relevance
“…While we have limited power to detect significance of small effects due to our relatively small sample size, the estimates for the C paths were all very small, accounting for only 1-4% of the variance in each measure. This finding is in contrast to the results of Harlaar et al (2007) who found significant shared environmental influences on reading performance through age 10, as well as to studies of younger children that reported significant shared environmental influences on word reading and related components (e.g., Byrne et al, 2005aByrne et al, , 2006Petrill, Deater-Deckard, Schatschneider, & Davis, 2005;Petrill et al, 2007;Petrill et al, 2006b;Samuelsson et al, 2005).…”
Section: Environmental Effectscontrasting
confidence: 56%
See 1 more Smart Citation
“…While we have limited power to detect significance of small effects due to our relatively small sample size, the estimates for the C paths were all very small, accounting for only 1-4% of the variance in each measure. This finding is in contrast to the results of Harlaar et al (2007) who found significant shared environmental influences on reading performance through age 10, as well as to studies of younger children that reported significant shared environmental influences on word reading and related components (e.g., Byrne et al, 2005aByrne et al, , 2006Petrill, Deater-Deckard, Schatschneider, & Davis, 2005;Petrill et al, 2007;Petrill et al, 2006b;Samuelsson et al, 2005).…”
Section: Environmental Effectscontrasting
confidence: 56%
“…Results of several studies suggest a core set of genetic influences common to many components of reading (e.g., Davis, Knopik, Olson, Wadsworth, & DeFries, 2001;Gayán & Olson, 2001Petrill, Deater-Deckard, Thompson, DeThorne, & Schatschneider, 2006b;Tiu et al, 2004). However, some studies have also found patterns of independent genetic effects for certain measures (Gayán & Olson, 2003;Petrill et al, 2007).…”
Section: Relation Between Word Reading and Comprehensionmentioning
confidence: 99%
“…In longitudinal studies, naming speed has proven to be rather stable and naming speed deficits appear to be persistent in nature (e.g., Powell, Stainthorp, & Stuart, 2014). Some part of this stability can be explained by genetic sources, as a strong genetic influence has been shown in RAN performance (e.g., Byrne et al, 2006;Christopher et al, 2015;Davis et al, 2001;Petrill, Deater-Deckard, Thompson, DeThorne, & Schatschneider, 2006;Petrill et al, 2010;Samuelsson et al, 2007). There is also recent research evidence for specific genes that have been associated with RAN performance (Naples, Chang, Katz, & Grigorenko, 2009), some of them the same as those previously associated with dyslexia (Rubenstein, Raskind, Berninger, Matsushita, & Wijsman, 2014).…”
Section: What Is Rapid Automatized Naming (Ran)?mentioning
confidence: 99%
“…al., 2006(Byrne, et. al., & 2007Petrill, Deater-Deckard et al, 2006, 2007. Other influences include practices in the home (Petrill et al, 2006(Petrill et al, , 2007, socio-economic level and ethnicity (McCoach et al, 2006), and in the case of reading fluency at least, peer influences within the classroom (Foorman et al, 2008).…”
Section: Review Of Related Literaturementioning
confidence: 99%